Which Book Do You Use, “Bahasa Inggris” by Kemendikbud or “Pathway to English” by Erlangga? A Content Analysis - Agustina Septua Sapta Sihotang; Sondang Manik; Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2021)
This research was conducted to find out the quality of two textbooks, “Bahasa Inggris” by Kemendikbud and “Pathway to English” by Erlangga for tenth grade based on the theory of Cunningsworth. The approach applied in this study was qualitative descriptive approach. In collecting and analyzing the data, the researcher used 7 out of 8 categories that consist of 40 checklist criteria to find out the result of this research. The data source was entered into checklist table to compare the materials in both books. The researcher then reported the table's results in terms of the aims and objectives, design and organization, linguistic content, skills, topic, methodology, and practical considerations. The writer found that both are good books and suitable for teachers and learners in Indonesia. “Bahasa Inggris” has met 80% fulfillment percentage of the checklist criteria and “Pathway to English” has met 87% fulfillment percentage. Both have weaknesses as well as strengths. This research can be beneficial for teachers to gain information about the quality and suitability of a textbook for learners and teachers so that teachers can decide which book is going to be used in the class. It is also beneficial to writers to improve the book, to publishers to know which book is good to publish and also to understand the definition of an excellent book. And the last, it is also useful to help other researchers to do the next research and to give information on how to do content analysis research.